Perlindungan Hukum terhadap Akta yang Dibuat oleh Notaris dan PPAT - Herlin Meilani Carolina; Kusyati Simare Mare; Maharani Nurwulandari (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
(This study examines the legal protection afforded to authentic deeds prepared by Notaries and Land Deed Officials (PPAT), as well as the factors that may cause such deeds to be disputed or deemed legally defective. In the Indonesian legal system, authentic deeds serve as crucial instruments of evidence, and the roles of Notaries and PPAT as public officials are essential in ensuring legal certainty and order. Using a normative juridical method, this research analyzes statutory regulations, legal doctrines, and court decisions. The findings indicate that legal protection for Notary and PPAT deeds derives from the inherent characteristics of authentic deeds, further reinforced by legislation such as the Notary Office Law and government regulations governing PPAT. Such protection includes authority-based safeguards, procedural guarantees during legal processes, and limitations of liability to the formal aspects of the deed. Nevertheless, deeds may still be challenged due to formal defects, material inaccuracies, authority violations, abuse of office, or disputes between the parties involved. This study underscores the importance of strict compliance with procedural requirements and jurisdictional boundaries to maintain the validity of deeds and strengthen the professionalism of Notaries and PPAT in providing legal certainty for the public.)